An An Analysis of Students’ Difficulties in Reading Comprehension at The Tenth Grade MA Al-Shighor: Analisis Kesulitan Siswa dalam Membaca Pemahaman di Kelas Sepuluh MA Al-Shighor - Puput, Putri Aliyanti (NextGen Education Review Journal, 2024)
This study aims to identify and understand the difficulties faced by tenth-grade students at MA AL-SHIGHOR in reading comprehension, as well as the internal and external factors affecting these difficulties. The research method used is descriptive qualitative, with data collection through questionnaires, interviews, and observations. The findings show that students experience difficulties in understanding texts at various levels, including literal, inferential, and critical comprehension. Factors influencing students' reading comprehension difficulties include a lack of vocabulary, sentence structure complexity, lack of reading interest, and an unconducive learning environment. Based on the conclusions of this study, there is a need for the development of more effective teaching methods to address students' reading difficulties.